2018
DOI: 10.1021/acsbiomaterials.7b00511
|View full text |Cite
|
Sign up to set email alerts
|

High Antifungal Activity against Candida Species of Monometallic and Bimetallic Nanoparticles Synthesized in Nanoreactors

Abstract: Among all novel challenges nowadays worldwide, infectious disease is probably one of the most important. It is wellknown that common treatments used include high doses of antibiotics, which are very invasive therapies for patients. These treatments are more intensive when the infection is related to multidrug resistant microorganisms. In this sense, in this work we report the use of reverse micelles to form less than 5 nm gold, silver, and gold−silver nanoparticles (NPs) with biological activity against five o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…Moreover, all fungal species including Candida, possess a cell membrane, consisting of phospholipids and a cell wall made up of mannoproteins, β-glucan-chitin, β-glucan. Therefore, the NPs need to bind and interact with the macromolecules of cell wall for interaction with the phospholipids, integral and peripheral proteins, and also ionic channels 6,33 . Studies also support the generation of ROS, due to oxidative stress on the microbial cell leading to disruption of cell membrane and cease of cellular activity, which finally leads to cell death 31,34,35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, all fungal species including Candida, possess a cell membrane, consisting of phospholipids and a cell wall made up of mannoproteins, β-glucan-chitin, β-glucan. Therefore, the NPs need to bind and interact with the macromolecules of cell wall for interaction with the phospholipids, integral and peripheral proteins, and also ionic channels 6,33 . Studies also support the generation of ROS, due to oxidative stress on the microbial cell leading to disruption of cell membrane and cease of cellular activity, which finally leads to cell death 31,34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…To combat the drug resistance, there is a need to search and modulate new therapeutics as antimicrobials and anticancer agents. Therefore, NPs have offered a potential solution to this problem 2,6 .…”
mentioning
confidence: 99%
“…Dose-dependent anticandidal activity of AgNPs has been previously reported. 26,35 Effects of ScAgNPs on extracellular hydrolytic enzymes of Candida spp…”
Section: Antimicrobial Activity Of Scagnpsmentioning
confidence: 99%
“…Kim et al 56 reported that AgNPs damage the cell wall and membrane of C. albicans due to the formation of "pits and holes" on the cells surface that inhibits the budding process and finally leads to cell death. Gutierrez et al 35 reported that the fungistatic effect of AgNPs was due to the inhibition of β-glucan synthase, and the fungicidal effect was due to changes in the cell wall integrity, and loss of its mechanic resistance that leads to the cell destruction by osmotic pressure variations. However, in another study, it has been reported that AgNPs promote mitochondrial dysfunctional apoptosis, phosphatidylserine externalization, DNA, and nuclear fragmentation, and the activation of metacaspases in C. albicans due to programmed cell death through generation and accumulation of intercellular ROS.…”
Section: Morphological and Ultrastructural Alteration Caused By Scagnpsmentioning
confidence: 99%
“…Microspheres may also cause deletion/mutation in gene FKS1 that will inhibit the activity of 1, 3β glucan synthase leading to disruption in cell glucan synthesis which results in cell wall damage ( Figure 11 ). 66 Moreover, the electrostatic interaction between the cell wall and antifungal material allows the antifungal material to invade the cell and produce ROS which in turns denatures enzymes and proteins and interact with DNA and RNA leading to cytotoxicity and cell apoptosis ( Figure 15 ). 67 Moreover, inhibition of Candida morphogenesis by Nys-MgO/CuO nanoparticles invariably inhibit biofilm formation.…”
Section: Effect On Virulence Factorsmentioning
confidence: 99%